PRACTICAL STRATEGIES FOR USING METAPHORS IN THERAPEUTIC COMMUNICATION AND CLINICAL PRACTICE - Angela CALANCEA (Psihologie)
Metaphors are essential components of therapeutic communication and clinical practice, serving as bridges between abstract concepts and tangible experiences. This article explores the multifaceted role of metaphors as cognitive tools for enhancing understanding, evoking emotional resonance, and facilitating psychological transformation. Drawing on foundational theoretical frameworks, including Conceptual Metaphor Theory and Embodied Cognition, the paper underscores the practical application of metaphors in diverse therapeutic contexts. Key strategies for selecting, adapting, and integrating metaphors into therapy are presented, alongside case studies illustrating their effectiveness in cognitive-behavioural therapy and Acceptance and Commitment Therapy. Emphasis is placed on cultural considerations, adaptation, and continuous innovation to ensure metaphors remain relevant and impactful. The findings highlight the transformative potential of metaphors in fostering emotional processing, cognitive flexibility, and therapeutic engagement. Recommendations are provided for practitioners aiming to refine their use of metaphors, with implications for future research in therapeutic discourse.